2014
DOI: 10.1586/17512433.2014.909281
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of recently approved drugs used to treat methicillin-resistantStaphylococcus aureusinfections in infants, children and adults

Abstract: Summary Methicillin-resistant Staphylococcus aureus (MRSA) remains a significant cause of morbidity in hospitalized infants. Over the past 15 years, several drugs have been approved for the treatment of S. aureus infections in adults (linezolid, quinupristin/dalfopristin, daptomycin, telavancin, tigecycline, and ceftaroline). The use of there majority of these drugs has extended into the treatment of MRSA infections in infants, frequently with minimal safety or dosing information. Only linezolid is approved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 78 publications
(153 reference statements)
1
13
0
2
Order By: Relevance
“…Daptomycin can be one of the choices for treating staphylococci-induced infections if there is a strong possibility based on local microbiological data or recent treatment history of vancomycin in an infected patient with MIC of > 1 μg/mL. Q/D comprises quinupristin and dalfopristin in a 30:70 ratio, which prevents protein synthesis in bacteria [134]. Studies have shown that Q/D with 0.7% has the highest resistance rate amongst MRSA strains (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin can be one of the choices for treating staphylococci-induced infections if there is a strong possibility based on local microbiological data or recent treatment history of vancomycin in an infected patient with MIC of > 1 μg/mL. Q/D comprises quinupristin and dalfopristin in a 30:70 ratio, which prevents protein synthesis in bacteria [134]. Studies have shown that Q/D with 0.7% has the highest resistance rate amongst MRSA strains (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“… 9 Daptomycin is renally excreted, and its systemic clearance in healthy adults is 0.011 L/kg/h. 10 Dosing must be adjusted for adult subjects who have impaired creatinine clearance. 11 , 12 In patients with chronic kidney disease stage 4 (creatinine clearance <30 mL/min) and in subjects undergoing hemodialysis or peritoneal dialysis, a dosage adjustment of daptomycin is recommended.…”
Section: Pharmacokinetics Of Daptomycinmentioning
confidence: 99%
“… 87 Daptomycin’s role in pediatric Gram-positive infections has been evaluated in several studies, and a good safety profile has been observed. 9 , 10 , 86 89 The IDSA MRSA treatment guidelines recommend the use of daptomycin (6–10 mg/kg/day) for managing MRSA bacteremia, infective endocarditis, acute hematogenous osteomyelitis, and septic arthritis in pediatric patients. 16 …”
Section: Daptomycin Use In Pediatric Patientsmentioning
confidence: 99%
“…1,2 It has an excellent activity against most methicillin-sensitive and methicillin-resistant Grampositive bacteria. 3 Linezolid was originally approved by Food and Drug Administration of United States for pediatric use in 2002, for treatment indicated infections, such as skin and skin structure infections, communityacquired and nosocomial pneumonia, and infections with vancomycinresistant Enterococcus faecium. 4 The advantages of linezolid compared to glycopeptide antibiotics include clinical and microbiological efficacy, excellent tissue penetration and lack of requirement for therapeutic drug monitoring.…”
Section: Introductionmentioning
confidence: 99%